Pharmacokinetics of Esomeprazole in Critically Ill Patients - Xu, Yanyan; Tian, Xin; Wang, Wei; Tian, Weiqiang; Zhang, Tao; Sun, Jian; Zhou, Qingyun; Shao, Chuxiao (Frontiers in Medicine, 2022)
Background: Esomeprazole, a potent proton pump inhibitor (PPI), is widely used for prevention of stress ulcer in intensive care unit (ICU) patients. Objective: This study investigates the pharmacokinetics (PK) of esomeprazole in critically ill patients. Methods: Adult ICU patients who required mechanical ventilation and had at least one additional risk factor for stress ulcer were eligible. All enrolled patients were received once-daily intravenous (IV) esomeprazole 40 mg. After the first dose of esomeprazole was administrated, serial blood samples were collected at 3, 5, 15, 30 minutes and 1, 2, 4, 6, 8 and 10 hours. Total sample concentrations of esomeprazole were measured by UPLC-MS/MS. Esomeprazole PK parameters were analyzed using noncompartmental analysis. Results: A total of 30 patients were evaluable. Their mean age was 61.97 years and body mass index (BMI) was 23.14. PK sampling on the first dose resulted in the following median (IQR) parameters: AUC0-∞ 8.06 (6.65-9.47) mg•h/L; MRT0-∞ 4.70 (3.89-5.51) h; t1/2 3.29 (2.7-3.87) h; V 24.89 (22.09-27.69) L; CL 6.13 (5.01-7.26) L/h; and Cmax 2.56 (2.30-2.82) mg/L. Conclusions: According to the label of esomeprazole, our study showed that different esomeprazole PK parameters in ICU patients compared with healthy volunteers. Esomeprazole has unique pharmacokinetic parameters in critically ill patients.